Palestinian acts of speaking together, apart: Subalterneities and the politics of fracture. - Bishara, Amahl A., 1976- (Tufts University. Tisch Library., 2017)
Palestinian citizens of Israel and Palestinians in the West Bank both protested in solidarity with Palestinians in Gaza during the 2014 war. They did so with what Charles Tilly would regard as distinct repertoires of contention, though they both referenced the same heritage of resistance. I argue that we should interrogate the boundaries that states establish to see how different forms of sovereignty and state violence shape resistance and expression. This approach highlights the role of the state in constituting the public sphere. The distinct subalterneities of these two Palestinian communities are a product not only of their political positions under Israeli rule, but also of the larger dynamics of fragmentation that separate them from one another. An analysis of their forms of protest demonstrates that in both cases, Palestinian protesters performed political community, whether by establishing a collective voice or by taking over space.